(untitled) (Al-Academy, 2025)
Television series have not been isolated from narrative and cinematic techniques but have benefited from them in developing their formal structure. The subjective camera is one of the most important techniques relied upon by directors to create a variety of narrative treatments that depend on how the camera is used to replace characters. Therefore, the researcher identified the research problem: What is the employment of the subjective camera in television series? Hence, the importance, objectives, and limits were determined. The research was divided into two main sections: The first section discussed the subjective camera, including concepts such as: an introduction to the concept of the subjective camera, the subjective point of view in television narrative, forms of narrative treatments of the subjective camera, and its uses in television series. The second section discussed the construction of the subjective camera: This section discussed how the subjective camera is constructed in terms of dealing with the elements of expressive language. A set of indicators was extracted. In the third chapter, the researcher chose the Chinese series "Journey Through the Night" (2020) in Chinese as it fits the temporal and thematic research boundaries and analyzed it. In the fourth chapter, the researcher reached a set of results, including: the director employs the subjective camera to enrich his narrative treatments within the series by transforming subjective aspects into operations that take various forms, such as recollection, hallucination, dream, and mental imagery. The researcher concluded that the employment of the subjective camera is a humanization of the audiovisual capture act of a camera placed in a control system that mimics emotions and feelings to produce a subjective point of view charged with emotions using the elements of expressive language. Thirdly: Recommendations Based on the foregoing, the researcher recommends that students study the aesthetic and dramatic employment of the subjective camera in the cinematography course. The research concluded with a list of references and an abstract in English. Conclusions: The use of the self-shot is a humanization of the act of audio-visual capture by a camera, placing it in a controlled system that simulates emotions and feelings to produce a personal point of view charged with emotions by means of elements of expressive language